2020
DOI: 10.1108/gkmc-01-2020-0007
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions regarding academic social networks for scholarly communications

Abstract: Purpose This study aims to investigate the perceptions of academics regarding the use and usefulness of academic social networks (ASNs) in the scholarly communication practices of faculty members in Kuwaiti Universities. Design/methodology/approach The study was conducted through a survey. In total, 100 faculty members from the discip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
0
1
Order By: Relevance
“…The results also revealed that intention to use leads at the end to the actual use, 46.1% of the variance in actual use is explained by the intention to use. While the literature supports the current findings (Al-Muomen et al , 2020; Segado-Boj et al , 2019), it is not necessarily the case for all researchers. Some scholars find that informal scholarly communication tools are not easy to use or even useful, but on the contrary, they found that informal tools may harm scholarly research and academia rather than benefiting it (Shehata et al , 2017; Shehata, 2015; Segado-Boj et al , 2019).…”
Section: Discussioncontrasting
confidence: 63%
“…The results also revealed that intention to use leads at the end to the actual use, 46.1% of the variance in actual use is explained by the intention to use. While the literature supports the current findings (Al-Muomen et al , 2020; Segado-Boj et al , 2019), it is not necessarily the case for all researchers. Some scholars find that informal scholarly communication tools are not easy to use or even useful, but on the contrary, they found that informal tools may harm scholarly research and academia rather than benefiting it (Shehata et al , 2017; Shehata, 2015; Segado-Boj et al , 2019).…”
Section: Discussioncontrasting
confidence: 63%